Production and stability of low amount fraction of formaldehyde in hydrogen gas standards. (29th March 2018) - Bacquart, Thomas; Perkins, Mark; Ferracci, Valerio; Martin, Nicholas A.; Resner, Kate; Ward, Michael K.M.; Cassidy, Nathan; Hook, Joshua B.; Brewer, Paul J.; Irvine, John T.C.; Connor, Paul A.; Murugan, Arul
Abstract: Formaldehyde is an intermediate of the steam methane reforming process for hydrogen production. According to International Standard ISO 14687-2 the amount fraction level of formaldehyde present in hydrogen supplied to fuel cell electric vehicles (FCEV) must not exceed 10 nmol mol −1 . The development of formaldehyde standards in hydrogen is crucial to validate the analytical results and ensure measurement reliability for the FCEV industry. NPL demonstrated that these standards can be gravimetrically prepared and validated at 10 μmol mol −1 with a shelf-life of 8 weeks (stability uncertainty <10%; k  = 1), but that formaldehyde degrades into methanol and dimethoxymethane, as measured by FTIR, GC-MS and SIFT-MS. The degradation kinetics is more rapid than predicted by thermodynamics, this may be due to the internal gas cylinder surface acting as a catalyst. The identification of by-products (methanol and dimethoxymethane) requires further investigation to establish any potential undesirable impacts to the FCEV. Highlights: Gravimetric preparation of Primary Reference Material of 10 μmol mol −1  CH2 O in H2 . CH2 O in H2 stability uncertainty below 10% ( k  = 1) with 8 weeks shelf-life. Formaldehyde degradation products methanol and dimethoxymethane (CO not observed). Identification of by-products using FTIR, GC-MS and novel technique SIFT-MS. Degradation kinetics more rapid than predicted by thermodynamics (surface catalyst).